PERILAKU SEKS DAN FAKTOR PENYEBAB TERJADINYA PADA REMAJA DI JORONG SIGUNTUR 1 KABUPATEN DHARMASRAYA - Hansari, Fitria Mai; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The problem in this research is The Sex Behavior and The casual Factor toward Teenagers in Jorong Siguntur I Kabupaten Dharmasraya. The purpose of this research was Â to (1) know the types of teenagersâ sex behavior, (2) know the casual internal factor of teenagersâ sex behavior, (3) know the casual external factor of teenagersâ sex behavior. The design of this research was descriptive research to draw a real situation. The population of this research was the teenagers of Jorong Siguntur I Kabupaten Dharmasraya. The number of population was 164 teenagers. This research was taken by using Stratified Random sampling. TheÂ sample was 33 teenagers as the sample that was taken based on the level of age.The result of the research found that: (1) types of teenagersâ sex behavior, such as, kissing, necking, flirting, masturbation, prostitution, and doing sex were low, (2) Casual internal factors of teenagersâ sex behavior, such as, rise of the sexual libido, knowledge, self control, emotional development, morality development, the strong desire, faith, and religion were moderate, (3) Casual external factor of teenagersâ sex behavior, such as, parents, friends, information resources (media), society environment, culture, and sex educatioan ware high. Based on the explanation above, the researcher suggests: (1) to all teenagers of Jorong Siguntur I Kabupaten Dharmasraya, they should be more careful with sex behavior, because it can break their future and can fall them on sexual intercourse, (2) then for parents, they should control all the development and activites of teenagers, they also should be able to give the belief to teenagers, so theyÂ can feel appreciated, (3) finally, for the further researcher, they can research about the tackling teenagersâ sex behavior.